Clinical significance of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios in breast cancer according to immunohistochemical subtypes and disease stage: Tiếng Anh - Phan, Thi Hang Giang; Tran, Thanh Loan; Tran, Thi Ai Nhi; Phan, Ngoc Dan Thanh; Truong, Thi Bich Phuong; Phan, Thi Minh Phuong (Tạp chí Y Dược Huế, 2026)
Background: Systemic inflammation plays a pivotal role in breast cancer (BC) progression and has been increasingly recognized as an important component associated with tumor aggressiveness. Inflammatory indices derived from routine blood tests, particularly the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), reflect the balance between tumor-promoting inflammatory responses and host antitumor immune surveillance. Objectives: To evaluate changes in systemic inflammatory markers in BC patients compared with healthy controls and to analyze their associations with TNM stage and immunohistochemical (IHC) subtypes. Methods: A descriptive cross-sectional study was conducted at Hue University Hospital, enrolling 24 newly diagnosed, untreated female BC patients and 24 healthy women. Clinical characteristics, TNM staging, and immunohistochemical (IHC) profiles (ER, PR, HER2, Ki-67) were collected. Patients were classified into early-stage (TNM I–IIA) and late-stage disease (TNM IIB–IV). Based on IHC profiles, tumors were categorized into Luminal A, Luminal B, HER2-positive, and triple-negative breast cancer (TNBC), with Luminal A considered low-risk and non-Luminal A subtypes considered higher-risk. NLR and PLR were calculated from peripheral blood counts and compared between groups, across disease stages, and IHC-based risk categories. Results: BC patients exhibited significantly higher NLR and PLR than controls (P < 0.05). Both indices were significantly elevated in BC patients with advanced-stage (IIB–IV) compared with early-stage (I–IIA). Patients with high-risk IHC subtypes, particularly non-Luminal A tumors, showed significantly higher NLR levels than those with Luminal A tumors. In contrast, conventional tumor markers, including CEA, CA 15-3, and C-reactive protein, did not show statistically significant differences across TNM stages or IHC subtypes. Conclusion: NLR and PLR are closely associated with disease stage and immunohistochemical subtypes in breast cancer. As simple, low-cost, and readily available parameters, these indices may provide complementary information to conventional markers for initial risk stratification and clinical assessment in breast cancer patients.